The Effectiveness and Safety of Favipiravir in COVID-19 Hospitalized Patients at Tertiary Referral Hospital, Bali, Indonesia - Damayanti, Herni; Sajinadiyasa, I Gede K; Risni, Hindun Wilda; Sauriasari, Rani (UI Scholars Hub, 2021)
COVID-19 is a major public health problem, with still questionable specific cure. Favipiravir is a COVID-19 antiviral that is potentially a therapy for COVID-19. This study aimed to analyze its effectivity and safety in moderate to critical hospitalized patients. This study was a retrospective cohort in a tertiary referral hospital in Denpasar City, Bali Province, Indonesia, from August 2020 to January 2021. There was a total of 192 patients; 96 in the favipiravir group and 96in the non-favipiravir group (remdesivir/oseltamivir). Effectivity was measured by assessing the clinical condition at the end of the isolation period of 14 days. The favipiravir group showed better clinical conditions than the non-favipiravir group (79.2% vs. 56.3%; adjusted RR = 2.196; 95% CI = 1.084 – 4.451; p-value= 0.029), seen from being free of fever and respiratory problems. Stratification analysis demonstrated that the clinical improvement was significantly differentin the severe/critical group in favor of favipiravir (RR = 1.573; 95% CI = 1.139-2.172). The most common non-serious adverse events (AE) found in the use offavipiravir were gastrointestinal disturbances (12.5%). In brief, favipiravir is effective in severe/critical cases, and less serious AE were found in its use. Appropriate treatment is expected to help in reducing the public health burden.